2018
DOI: 10.1002/jssc.201701137
|View full text |Cite
|
Sign up to set email alerts
|

Application of micro‐solid‐phase extraction for the on‐site extraction of heterocyclic aromatic amines in seawater

Abstract: An efficient on‐site extraction technique to determine carcinogenic heterocyclic aromatic amines in seawater has been reported. A micro‐solid‐phase extraction device placed inside a portable battery‐operated pump was used for the on‐site extraction of seawater samples. Before on‐site applications, parameters that influence the extraction efficiency (extraction time, type of sorbent materials, suitable desorption solvent, desorption time, and sample volume) were investigated and optimized in the laboratory. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…There are other kinds of extraction and clean‐up methods used for the analysis of HAAs in foodstuffs. As shown in Table , these methods include pressurized liquid extraction (Khan, Busquets, Santos, & Puignou, ), supercritical fluid extraction (De Andres, Zougagh, Castaneda, & Rios, ), accelerated solvent extraction (Ouyang, Li, Tang, Jin, & Li, ), air‐agitated cloud‐point extraction (Vichapong et al., ), microsolid‐phase extraction (µ‐SPE; Basheer, ; Zhang, Li, & Xiao, ), and QuEChERS technique (Hsiao et al., ). It is worth mentioning that μ‐SPE is advantageous over SPME.…”
Section: Extraction and Clean‐up Methods For Haasmentioning
confidence: 99%
See 2 more Smart Citations
“…There are other kinds of extraction and clean‐up methods used for the analysis of HAAs in foodstuffs. As shown in Table , these methods include pressurized liquid extraction (Khan, Busquets, Santos, & Puignou, ), supercritical fluid extraction (De Andres, Zougagh, Castaneda, & Rios, ), accelerated solvent extraction (Ouyang, Li, Tang, Jin, & Li, ), air‐agitated cloud‐point extraction (Vichapong et al., ), microsolid‐phase extraction (µ‐SPE; Basheer, ; Zhang, Li, & Xiao, ), and QuEChERS technique (Hsiao et al., ). It is worth mentioning that μ‐SPE is advantageous over SPME.…”
Section: Extraction and Clean‐up Methods For Haasmentioning
confidence: 99%
“…HPLC is the most common technique applied for the analysis of HAAs because it does not require derivatization process and requires minimal preparation. Over the last two decades, a number of LC‐based studies (summarized in Table ) by coupling with different kinds of detectors have been reported for the analysis of HAAs in foodstuffs including LC‐DAD (Agudelo Mesa et al., ; Cai et al., ; Cárdenes et al., ; Janoszka, Blaszczyk, Damasiewicz‐Bodzek, & Sajewicz, ; Melo et al., ; Özdestan et al., ; Tan et al., ), LC‐ECD (Bermudo, Ruiz‐Calero, Puignou, & Galceran, ; Martin‐Calero et al., ), LC‐FLD (Basheer, ; Jautz et al., ; Martín‐Calero et al., ; Martin‐Calero, Tejral, Ayala, Gonzalez, & Afonso, ; Ristic, Cichna, & Sontag, ), LC‐UVD (Aeenehvand et al., ; Yao et al., ; Zhang et al., ; Zhang et al., ), LC‐PDA (Vichapong et al., ; Vichapong, Srijaranai, Santaladchaiyakit, Kanchanamayoon, & Burakham, ), LC‐amperometric detector (Maria Bueno, Angel Marin, Maria Contento, & Rios, ), and HPLC‐coulometric electrode array detection (Gerbl, Cichna, Zsivkovits, Knasmüller, & Sontag, ).…”
Section: Instrumental Analytical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although lacking evidence to support the hypothesis that excessive uptake of HAs could directly cause cancer, the International Agency for Research on Cancer has already decided a limitation of HAs . HAs have been discovered in different matrices . Most of the researchers have isolated and identified them in food samples and related substances.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the researchers have isolated and identified them in food samples and related substances. For instance, barbecue, roast fish, cooking residues (such as pan residues and cooking smoke), alcoholic beverages, and many other compounds have been reported to contain trace of HAs . Besides, in biological samples (such as serum, hair, bile, human milk, urine, and so on), HAs have been detected .…”
Section: Introductionmentioning
confidence: 99%